SISTEMA DE ADQUISICIÓN DE DATOS Y TRASMISIÓN INALÁMBRICA BASADO EN PC - Cómina, Germán (1999)
In this paper, the construction of a wireless data acquisition system is described. The system enable us monitoring process that are developed in hazardous environments, or other physical phenomena that must be realized far away the laboratory. Three basic units compose the system: analogic to digital converter with transmitter, receiver, and the PC with application software.